VapC toxins drive cellular dormancy under uranium stress for the extreme thermoacidophile Metallosphaera prunae. (7th July 2017) - Mukherjee, Arpan; Wheaton, Garrett H.; Counts, James A.; Ijeomah, Brenda; Desai, Jigar; Kelly, Robert M.
Summary: When abruptly exposed to toxic levels of hexavalent uranium, the extremely thermoacidophilic archaeon Metallosphaera prunae, originally isolated from an abandoned uranium mine, ceased to grow, and concomitantly exhibited heightened levels of cytosolic ribonuclease activity that corresponded to substantial degradation of cellular RNA. The M. prunae transcriptome during 'uranium‐shock' implicated VapC toxins as possible causative agents of the observed RNA degradation. Identifiable VapC toxins and PIN‐domain proteins encoded in the M. prunae genome were produced and characterized, three of which (VapC4, VapC7, VapC8) substantially degraded M. prunae rRNA in vitro . RNA cleavage specificity for these VapCs mapped to motifs within M. prunae rRNA. Furthermore, based on frequency of cleavage sequences, putative target mRNAs for these VapCs were identified; these were closely associated with translation, transcription, and replication. It is interesting to note that Metallosphaera sedula, a member of the same genus and which has a nearly identical genome sequence but not isolated from a uranium‐rich biotope, showed no evidence of dormancy when exposed to this metal. M. prunae utilizes VapC toxins for post‐transcriptional regulation under uranium stress to enter a cellular dormant state, thereby providing an adaptive response to what would otherwise be a deleterious environmental perturbation.